Stringent Internal Quality Control Procedures in Chemical Pathology Lead to Better Performance in External Proficiency Testing - Atzaz, Noreen; Mehnaz; Zuhra, Fatima Tuz; Muneer, Siraj; Ali, Haider; Saeed, Sami (Journal of Rawalpindi Medical College, 2023)
Objective: To assess impact of stringent Internal Quality Control (IQC) checks on performance of proficiency testing Material and methods: This was a Prospective study conducted between September 2020 and April 2021 at Chemical pathology lab of Fauji Foundation Hospital Rawalpindi. External quality control data (EQC) from the month of September was evaluated. As part of corrective action plan IQC checks were enforced, internal quality control (IQC) data of the month of September 2020 and April 2022 were assessed. Performance characteristics of routine chemistry analytes coefficient of variance (CV), standard deviations (SD)and Bias were calculated and compared using paired –T- test. Results: Proficiency testing report (NEQAPP) of cycle 10 round 1 showed 11% External Quality Control (EQC) failure among 18 biochemical parameters. Serum Creatinine and Total Protein failed acceptability criteria with Z-score of greater than 2. As part of corrective action IQC checks were done, which led to improvement in CV (SD) of these parameters. The next EQC lab report for routine chemistry analytes met the acceptability criteria with z-scores of all anaytes being less than 2. Conclusion: Precise & accurate IQC results lead to better performance in EQC results